Penggunaan lemari pengasapan ikan untuk meningkatkan produksi pada industri rumah tangga di Kabupaten Pulau Morotai - Bambang Tjiroso; Rinto M. Nur; Ariestha W. Bustan (DEDIKASI, 2020)
One processed fish product that is favored by many people on Morotai Island is smoked fish. Although much popular, the smoked fish home industry on Morotai Island does not routinely produce smoked fish every day. Smoked fish processing still uses conventional equipments. The equipment which is open makes it difficult for partners to maximize the use of combustion fumes to smoked fish. Much smoke is wasted causing the use of fuel waste and smoking time becomes longer around 4 to 8 hours, so that in one day the partners only do one smoking process. Besides that, with the condition of smoking equipment that is open in the event of strong winds or heavy rain the partner cannot carry out the process of smoked fish. The purpose of this community service activities is to replace conventional (open) fish smoking equipment with modern cabinet / cabinet type smoking equipment to increase smoked fish production. The steps taken are the manufacture of smoking equipment, initial testing in order to maximize the use of fuel and temperature in the smoking cabinet. The next step is testing the estimated time of smoking fish and the capacity of fish in a single production. After the testing phase is completed, it is continued with the socialization stage for the manufacture and operation of the fish fume cupboard tool to partners as well as the production process assistance. The results of the service show that the amount of fuel needed is less. In addition, the time needed in one production is faster (2-3 hours) and partners can produce smoked fish every day.